Implementasi Penggunaan Media Big Book Berbasis Dongeng dalam Meningkatkan Kemampuan Membaca Interaktif Siswa Kelas II MI Islamiyah Jatimulya - Syamsul Falah; Khalimatus Sadiah; Muhammad Duror An Nashich (La-Tahzan: Jurnal Pendidikan Islam, 2024)
This thesis is the result of research regarding the Implementation of the Use of Fairy Tale-Based Big Book Media in Improving the Interactive Reading Ability of Class II Students at MI Islamiyah Jatimulya. As for the background of this research, the researcher found indications of the problem of students' lack of concentration in learning and the low reading ability of class II students, monotonous teacher learning methods and the absence of use of interesting learning media which had an impact on students' lack of learning motivation and enthusiasm in learning. so that the teaching and learning process tends to be passive. This type of research is field research. The method used in this research is a qualitative method. To analyze the problems above, researchers used the interactive data analysis model from Miles and Huberman which involves four stages of data analysis, namely data collection, data reduction, data presentation, and data verification. This research aims to improve the interactive reading skills of class II students at MI Islamiyah Jatimulya. The subjects of this research were 20 class II students consisting of 10 male students and 10 female students. Data collection techniques in this research are observation and interviews. Interviews were used to see the use of fairy tale-based big book media. Meanwhile, observation is used to see student activities in the application of fairy tale-based big book media in classroom learning. The results of the research show that there is an increase in student learning activities when implementing fairy tale-based big book media. A total of 14 students obtained a score percentage of 88% in the "good" category. A total of 4 students obtained a percentage score of 92% in the "very good" category and there were only 2 students who obtained a low percentage score, namely 76% in the "not good" category. The indicators of reading difficulties experienced by these students are not being able to pronounce vowel diphthong letter combinations (nya, nyi, nga, ngi...) and having help to read and spell syllables